SOSIALISASI APLIKASI UNTUK MELAKUKAN DETEKSI DINI KECANDUAN PERMAINAN ONLINE PADA SISWA SMK N 1 KLARI KARAWANG - Masruriyah, Anis Fitri Nur; Wahiddin, Deden; Novita, Hilda Yulia; Awal, Elsa Elvira (ABDI KAMI: Jurnal Pengabdian Kepada Masyarakat, 2022)
The global COVID-19 pandemic has an impact on people's activities in the world, including in Indonesia. The policies of each country to overcome this condition also vary, one of which is the Indonesian government which imposes limited face-to-face activities offline. Many activities must be carried out online to minimize the transmission of COVID-19. Finally, this has an impact on many people who spend time with their gadgets to play permainans with cellphones, laptops or other electronic media. Playing permainans has benefits for relaxation from the fatigue of online activities, but if this continues it will result in permainan addiction. So that community service activities for the socialization of permainan addiction detection applications are carried out, so that users are able to control the use of devices when playing permainans. So, if an addiction is detected, you can ask experts for help, for school children you can have an initial consultation with a Counseling Guidance teacher.